Pertanggungjawaban Individu dalam Peristiwa Pidana dengan Tenaga Bersama Melakukan Kekerasan Kepada Orang Lain: Eksaminasi Putusan Nomor 849/Pid.B/2020/PN Jkt.Tim - Fariz Rifqi Hasbi (Jurnal Hukum Lex Generalis, 2025)
Within the community, violence is still common. Whether it's as a reaction to a violation of customary norms or violations of legal norms, such as beatings of thieves who are caught red-handed and incidents of brawls, or violence committed for a specific purpose, such as the persecution of someone because they don't want to follow their will. But what is certain is that violence will cause harm to victims and/or public order, both physical and non-physical, ranging from damage to property, public facilities, minor injuries to victims, serious injuries to loss of life. Therefore violence is included in acts against formal law and material legal acts. As a legal phenomenon in the social environment, violence can be carried out individually or together. Collective violence is commonly referred to as beatings, that is, with joint force to abuse or destroy property. However, law enforcement against these crimes will experience difficulties if the parties participating in the beating run away, or in other words if only 1 (one) person was caught among the alleged perpetrators of the beating. Therefore, in enforcing the law against bullying incidents, it is necessary to have an alternative in applying the law so that it can ensnare the perpetrators of the beating, especially if only 1 (one) person is arrested and processed under criminal procedural law. The purpose of this study is to find out which articles in the Indonesian Criminal Code regulate the crime of beatings and to find out the application of Article 351 concerning persecution of beatings. The research method in this research is normative juridical research which is also known as doctrinal research, which is a research that analyzes both law as law as it is written in the book, as well as law as it is decided by judge through judicial process. The targeted output is a Sinta accredited journal.